A rare missense Duchenne muscular dystrophy gene variant in a family with muscular dystrophy from Turkey - Tokgün, Onur; Albuz, Burcu; Karagenç, Nedim; Erdoğan, Çağdaş; Demiray, Aydın; Akça, Hakan (The European Research Journal, 2022)
Objectives: Duchenne and Becker muscular dystrophies (DMD/BMD) are muscle diseases that show X-linked recessive inheritance. The disease occurs depending on large mutations, deletions/duplications, small mutations, point mutations and mid-intronic mutations of the gene encoding the protein called dystrophin. Therefore, in this study, we aimed to investigate the pathogenic variants of DMD in the affected family. Methods: A 23-year-old male who had weakness in the muscles, difficulty climbing the stairs, frequent falls at the age of seven was referred to the Medical Genetics department for an initial diagnosis of DMD/BMD. His siblings also suffered from similar symptoms. Therefore, eight individuals from the same family were included in the study. MLPA analysis was performed to evaluate deletion/duplication and variants of the DMD gene were evaluated by targeted NGS. Sophia DDM algorithms were used for the bioinformatics analysis of data, and the pathogenicity of the mutations was evaluated based on in silico prediction tools. Results: Allelic variants were identified in 8 individuals of the family including two suspected patients and six suspected obligatory carriers. NGS analysis revealed that proband and his nephew were hemizygous for pathogenic c.10018T> C (p.Cys3340Arg, C3340R) mutation and mother, two sisters and niece were carriers. Conclusions: C3340R mutation was first reported in a Taiwanese BMD patient among the 23 different pathologic changes. This variant identified as pathogenic because of being highly conserved cysteine substitution in the dystroglycan-binding domain of dystrophin. This study has the importance of reporting an infrequent pathogenic mutation, C3340R, in two patients and four suspected obligatory carriers of a Turkish family.